A multiprocess machine tool for compound micromachining - Rahman, M.; Asad, A.B.M.A; Masaki, T.; Saleh, Tanveer; Wong, Y.S.; Senthil Kumar, A. (2010)
Compoundmicromachiningisthemostpromisingtechnologyfortheproductionofminiaturizedparts and thistechnologyisbecomingincreasinglymoreimportantandpopularbecauseofagrowing demandforindustrialproducts,withanincreasednumbernotonlyoffunctionsbutalsoofreduced dimensions,higherdimensionalaccuracyandbettersurfacefinish.Compoundmicromachining processesthatcombinemultipleconventionalandnon-conventionalmicromachiningprocesseshave the capabilitytofabricatehighaspectratiomicrostructureswithparamountdimensionalaccuracy. Such machiningshouldbecarriedoutonthesamemachinewithminimumchangeofsetups.Atthe same time,on-machinetoolfabricationalongwithon-machinetoolandworkpiecemeasurement facilitiesshouldalsobeavailableforfurtherenhancementofthefunctionalityofthemachineand higher productivity.Inordertoachieveeffectiveimplementationofcompoundmicromachining techniques,thisresearchseekstoaddressfourimportantareas,namely(a)developmentofamachine tool capableofbothconventionalmicromachiningincludingmicroturning,micromilling,etc.,andnon- conventionalmicromachiningincludingmicroelectricaldischargemachining(micro-EDM),wire-cut electricaldischargemachining(WEDM),etc.;(b)processcontrol;(c)processdevelopmenttoachieve the necessaryaccuracyandqualityand(d)on-machinemeasurementandinspection.Anintegrated effort intotheseareashasresultedinsuccessfulfabricationofmicrostructuresthatareabletomeetthe miniaturizationdemandsoftheindustry.Thispaperpresentsafewtool-basedapproachesthat integratemicro-EDM,micro-EDG,microturningandmicrogrindingtoproduceminiaturecomponents on thesamemachinetoolplatforminordertodemonstratethecapabilitiesofcompound micromachining.